Snake Venom and Ecology - Manjur Shah, Mohammad; Sharif, Umar; Rufai Buhari, Tijjani; Sabiu Imam, Tijjani (IntechOpen, 2022)
Snakes play a very important role in our ecosystem, helping to balance the food web and maintain biodiversity on Earth. This book highlights the extreme ecological importance of snakes with chapters on snake venom and its therapeutic potential and the ecology of some selected snake species.